Unpublished Conjectures to the Appendix Vergiliana by F. Korsch, G. Saenger, and A. Sonny - Shumilin, Mikhail (Hyperboreus, 2023)
The paper is dedicated to the publication of a set of previously unpublished conjectures to the so-called Appendix Vergiliana (the corpus of works ascribed to Vergil other than the three canonical ones) by three scholars of the Russian Empire, Fyodor E. Korsch (1843–1915), Grigory E. Saenger (1853–1919), and Adolf I. Sonny (1861–1922). The conjectures probably all date between 1901 and 1919 and are extant in the correspondence of the three scholars and Saenger’s marginal handwritten notes on the oﬀprints of his papers, both types of sources preserved in the scholarly archives of Saenger and Korsch in the Archive of the Russian Academy of Sciences, Moscow (Funds 504 and 558 respectively).